2023
DOI: 10.3390/agronomy13020470
|View full text |Cite
|
Sign up to set email alerts
|

Application of Dairy Effluents to Pastures Affects Soil Nitrogen Dynamics and Microbial Activity

Abstract: The use of farm dairy effluents (FDE) has become a promising alternative to increase pasture yield while reducing the environmental impact of waste accumulation into streams, but other environmental implications should be considered. The present study aimed to assess the effect of application of either raw FDE or lagoon-stored FDE compared to dissolved urea or a non-amended control on N2O emission, soil N dynamics, functional microbial activity, and the yield and N-use efficiency of a fescue pasture. The norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…Therefore, considering that low temperatures decrease the activity of various microorganisms and slow the rate of organic matter degradation, it was expected that the TOC in DE would be higher in winter sampling and, accordingly, higher TN and lower cation content concentrations were found in the Lagoon samples ( Table 1 and Table S1 ). Previous studies showed similar results [ 38 , 50 ]. Thauera species were as identified as major denitrifying bacteria that occurred in digested DE [ 51 ], and their increase revealed in the Lagoon samples during the warmest sampling may suggest a role in N removal, as postulated by Ren et al [ 34 ].…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, considering that low temperatures decrease the activity of various microorganisms and slow the rate of organic matter degradation, it was expected that the TOC in DE would be higher in winter sampling and, accordingly, higher TN and lower cation content concentrations were found in the Lagoon samples ( Table 1 and Table S1 ). Previous studies showed similar results [ 38 , 50 ]. Thauera species were as identified as major denitrifying bacteria that occurred in digested DE [ 51 ], and their increase revealed in the Lagoon samples during the warmest sampling may suggest a role in N removal, as postulated by Ren et al [ 34 ].…”
Section: Discussionsupporting
confidence: 83%
“…When organic materials are added to the soil, the carbon is broken down by soil microorganisms and incorporated into the soil organic matter [3]. Studies have shown that the application of FDE to soil can increase the soil's mineralization potential and improve its microbial activity and functional diversity [4]. The mineralization of FDE in the soil can also contribute to the release of nitrogen and other nutrients that can be taken up by plants [5].…”
Section: Introductionmentioning
confidence: 99%